ENHANCING ENGLISH LISTENING SKILLS THROUGH STORY-BASED YOUTUBE CONTENT - NURILLO JAMBILOV XABIBILLOYEVICH (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Listening is one of the most fundamental yet challenging skills in learning a foreign language. In English as a Foreign Language (EFL) contexts, learners often struggle to understand authentic spoken input due to limited exposure, lack of motivation, and insufficient listening strategies. With the rapid development of digital technologies, online platforms such as YouTube have become powerful tools for language learning. This article explores the effectiveness of using story-based YouTube content to enhance English listening skills among EFL learners. The study discusses theoretical foundations of listening comprehension, the pedagogical value of storytelling, and practical classroom applications of YouTube stories. The findings suggest that story-based listening materials on YouTube significantly improve learners’ listening comprehension, vocabulary acquisition, pronunciation awareness, and motivation. The article concludes that integrating YouTube stories into listening instruction is an effective and learner-centered approach in modern English language teaching.